2013
DOI: 10.1002/gcc.22058
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of chromosome 11 breakpoints and the areas of deletion and amplification in patients with newly diagnosed acute myeloid leukemia

Abstract: Chromosome 11 abnormalities are found in many hematological malignancies. In acute myeloid leukemia (AML), a proto-oncogene MLL (11q23.3) is frequently altered. However, rearrangements involving other regions of chromosome 11 have been reported. Therefore, we have characterized the chromosome 11 breakpoints and common deleted and amplified areas in the bone marrow or peripheral blood cells of newly diagnosed patients with AML. Using molecular-cytogenetic methods (multicolor fluorescence in situ hybridization (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…These observations are independent of the homologous miR-16 cluster embedded in SMC4 on chromosome 3q26, which shows no significant expression or DNA methylation changes in association with AML (Additional file 8). Similar results have been reported for adult CLL [32]. Taken together this data suggests an alternate mode of regulation for the miR-15a/16-1 cluster, outside of the DLEU2 promoter region.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…These observations are independent of the homologous miR-16 cluster embedded in SMC4 on chromosome 3q26, which shows no significant expression or DNA methylation changes in association with AML (Additional file 8). Similar results have been reported for adult CLL [32]. Taken together this data suggests an alternate mode of regulation for the miR-15a/16-1 cluster, outside of the DLEU2 promoter region.…”
Section: Resultssupporting
confidence: 89%
“…Recent studies in adult CLL have also identified a negative correlation between DLEU2 promoter methylation ( DLEU2/Alt1) and gene expression [32]. Interestingly there was no change in gene expression for any other genes in this region (TRIM13 = 1.75 FC; DLEU1 = 1.05 FC.…”
Section: Resultsmentioning
confidence: 94%
“…However, no association was observed in a subsequent study (26). The CNV at this locus have also been reported to be affected in different types of cancer (27)(28)(29). Interestingly, the LRP5 gene is located 838 kb downstream of the 11q13.2 locus, and has been shown to regulate development of lung microvessels and alveolar formation through the angiopoietin-Tie2 pathway (30).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, chromosome 11 features in the cytogenetic analysis of both BC and AML [6,7]. In AML, chromosome 11 is one of the most common targets of gene amplification [8].…”
Section: Discussionmentioning
confidence: 99%
“…Amplicons on chromosome 11 may vary in size, but they usually involve the long arm of the chromosome, particularly the region 11q23, where an MLL proto-oncogene (myeloid/lymphoid leukemia or mixed-lineage leukemia (trithorax homolog [,]Drosophila)) is located [9]. In BC, nonrandom abnormalities of chromosome 11 are frequently reported, with involvement of 11p15, 11q13, and 11q23 [6]. Trisomy 11 is associated with unfavorable prognosis in AML but not with NPM1 or KIT mutation [10].…”
Section: Discussionmentioning
confidence: 99%